Pow! - Mo, Yan (Seagull Books, 2012)
[In this novel by the 2012 Nobel Laureate in Literature], "a benign old monk listens to a prospective novice's tale of depravity, violence and carnivorous excess while a nice little family drama--in which nearly everyone dies--unfurls ... As his dual narratives merge and feather into one another, each informing and illuminating the other, Mo Yan probes the character and lifestyle of modern China."--Dust jacket.